Contextual factors associated with late HIV diagnosis in people aged 50 years and older in Brazil (2017–2022): Late HIV diagnosis in adults aged 50 years and older - Souza, Denise Eliziana de; Amaral, Léa de Freitas; Silva, Christiano Barbosa da; Ferreira, Fernanda Letícia dos Santos (Brazilian Journal of Sexually Transmitted Diseases, 2025)
Introduction: Population aging has health implications beyond individual aspects. People aged 50 years or older may have a lower perception of risk, less access to preventive strategies, and greater structural vulnerability to late diagnosis, with negative impacts on clinical outcomes and quality of life. Objective: To identify social determinants associated with late diagnosis of HIV infection in people aged 50 years or older in Brazil. Methods: A cross-sectional ecological study with data from the federation units in the period from 2017 to 2022, using negative binomial regression modeling to estimate associations between socioeconomic variables and health access indicators with the proportion of late diagnosis (CD4<200 cells/mm3). Results: 43,395 cases of HIV in people aged 50 years or older, 32.9% of them late. A statistically significant direct association was identified between late diagnosis of HIV and the illiteracy rate (RR>1), and inverse and significant associations with the aging rate and distribution of rapid tests (RR<0). In terms of population, these magnitudes represent substantial impacts on late diagnoses in the population aged 50 years or older. Conclusion: It was found that higher rates of illiteracy increase the occurrence of late diagnoses, while greater population aging and greater distribution of rapid tests reduce this risk.